Peritoneal pseudocyst: a rare complication of peritoneal dialysis - Sarabia-Pérez, Yoselin Julisa; Heredia-Montaño, Mónica; Vela- Ramos, Montserrath Ashanti; Díaz-Barrientos, Cheryl Zilahy; Sosa-Sánchez, Omar; Zayas-Borquez, Rogelio (International Journal of Research in Medical Sciences, 2023)
Peritoneal dialysis is a method of renal function replacement which has a series of advantages like greater autonomy of the patient, but it also has disadvantages, like leakage, peritonitis and abdominal wall weakness. We present the case of a patient with a history of renal replacement therapy managed on peritoneal dialysis which presents a rare complication that required surgical treatment. A peritoneal pseudocyst enclosing the dialysis catheter tip is a rare complication of peritoneal dialysis. The pathogenesis of pseudocyst formation is not yet explained; however, bacterial infections and abdominal surgery seem to be predisposing factors. It is important to know how peritoneal dialysis works and the early and late complications of this renal function replacement therapy. Further studies are needed in this area to look into the pathophysiology and evaluate the contributing factors for the development of peritoneal pseudocyst and its treatment.